To sculpt a life ... Abueva ... an intimate view [videorecording] - Medina, Susan Calo.; Quintos, Floy.; GMA 7 (Television station : Quezon City).; National Commission for the Culture and the Arts.; Travel Time (Television program). (Manila Travel Time, 1997)
Features Napoleon Abueva, the national artist for the visual arts with his sculpture gallery, garden of sculpture and his life.
Documentary.
VHS.
Keywords: Abueva, Napoleon Veloso; Artists, Filipino; Arts, Philippine; Sculpture -- Philippines